2017
DOI: 10.1088/2058-6272/aa57e4
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of organosilicone thin film from hexamethyldisiloxane (HMDSO) with 50 kHz/33 MHz dual-frequency atmospheric-pressure plasma jet

Abstract: The deposition of organosilicone thin films from hexamethyldisiloxane(HMDSO) by using a dual-frequency (50 kHz/33 MHz) atmospheric-pressure micro-plasma jet with an admixture of a small volume of HMDSO and Ar was investigated. The topography was measured by using scanning electron microscopy. The chemical bond and composition of these films were analyzed by Fourier transform infrared spectroscopy (FTIR) and x-ray photoelectron spectroscopy. The results indicated that the as-deposited film was constituted by si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Absorbance intensities at 1030,1055, 1107 and 1316 cm −1 are assigned to a C–O stretch, asymmetric in-plane ring stretch, asymmetric bridge C–O–C and CH wagging vibrations [ 10 ], respectively, which is a typical infrared spectrum of untreated cellulose in cotton fabric. In Figure 6 , characteristic peaks at 800 and 973 cm −1 are assigned to Si–O–Si bending vibration and Si–O–C symmetric stretching vibrations [ 14 ]. The peaks at 2958 and 1256 cm −1 assigned to CH 3 asymmetric stretching and Si–CH 3 symmetric bending are also observed in both N 2 and O 2 plasma treated samples, which are absent in the untreated cotton, indicated that Si–CH 3 groups in the structure of the deposited coating formed by HMDSO plasma polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbance intensities at 1030,1055, 1107 and 1316 cm −1 are assigned to a C–O stretch, asymmetric in-plane ring stretch, asymmetric bridge C–O–C and CH wagging vibrations [ 10 ], respectively, which is a typical infrared spectrum of untreated cellulose in cotton fabric. In Figure 6 , characteristic peaks at 800 and 973 cm −1 are assigned to Si–O–Si bending vibration and Si–O–C symmetric stretching vibrations [ 14 ]. The peaks at 2958 and 1256 cm −1 assigned to CH 3 asymmetric stretching and Si–CH 3 symmetric bending are also observed in both N 2 and O 2 plasma treated samples, which are absent in the untreated cotton, indicated that Si–CH 3 groups in the structure of the deposited coating formed by HMDSO plasma polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma induced surface modifications (including polymerization) do not damage the mechanical properties of the fiber and bulk fabrics, because the depth of modification on the fiber surface is just less than ~10 nm [ 13 ]. Furthermore, recent technological advances in atmospheric pressure plasma generation and applications have tremendously improved the commercial viability of the traditional vacuum plasma technology in allowing continuous operation at a regular plant environment while preserving many of the benefit of plasma particle/substrate interactions with the surface being modified [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organosilicon thin films, obtained by plasma polymerization in plasma‐enhanced chemical vapor deposition (PECVD) systems from precursors containing silicon, are well‐known for their wide range of modern technological applications, such as corrosion protective coatings, humidity and gas sensing, hydrophobic layers, hard coatings, and optical/electrical interlayers . Hexamethyldisiloxane (HMDSO) is among the frequently used precursors because of its nontoxicity and its relatively low cost …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Hexamethyldisiloxane (HMDSO) is among the frequently used precursors because of its nontoxicity and its relatively low cost. 16 Plasma treatment, depending on the gas type, experimental conditions, and final desired properties, is well established to treat different materials surfaces (polymer, silica, metal oxide, semiconductor, etc). 17,18 The plasma-polymerized organosilicon thin films can be considered as a polymer substrate, and consequently, a plasma posttreatment of its surface can be elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…However,compared with traditional APPJ driven by AC power supply, the APPJ excited by nanosecond or microsecond pulses can avoid local overheat of micro-discharge and improve discharge homogeneity [40,41]. Considering the excellent electrical and corrosion resistance of SiC x H y O z film [42,43], this paper adopts nanosecond pulse driven APPJ to deposit SiC x H y O z film on epoxy resin surface to improve its insulation performance. The surface properties of EP before and after the treatment were evaluated by atomic force microscope (AFM), scanning electron microscope (SEM), x-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (ATR-FTIR) and high resistance meter.…”
Section: Introductionmentioning
confidence: 99%